Pengaruh Persepsi Terhadap Dukungan Organisasi dan Kecerdasan Emosi Terhadap Konflik Pekerjaan - Keluarga - Kusendi, Rahmanto (Bina Nusantara University, 2011)
This study aimed to investigate the influence of perceptions of organizational support and emotional intelligence to work - family conflict in an organization. This study involved 60 employees of private respondent is married and works in three service companies in Jakarta. Samples distributed in 85 respondents in the three companies, but that pass the requirements of the study amounted to 60 people. Hypothesis testing using the formula of normality One - Sample Kolmogorov - Smirnov and statistical analysis performed using simple linear regression. The results showed that perceptions of organizational support has a direct impact on the level of work-family conflict with a significance level of p = 0024. In the results of this study also found that emotional intelligence does not serve as a means to intervene between the perception of organizational support with work-family conflict.